2017
DOI: 10.1631/jzus.b1600064
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells

Abstract: Abstract:Objective: Low-density granulocytes (LDGs) can form neutrophil extracellular traps (NETs) spontaneously and excessively. When peripheral blood mononuclear cells (PBMCs) are used for studying T lymphocytes, LDGs contained in the PBMCs may decrease the threshold of activating T lymphocytes by forming NETs. This study focused on the profiles of LDGs in common autoimmune diseases and methods for removing LDGs from PBMCs. Methods: The percentages of LDGs in PBMCs from 55 patients with dermatomyositis (DM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These results confirm that LDGs indeed can inhibit the secretion of IFN-γ in T cells through some mechanism. However, a previous study by Zhang et al had reported an opposite impact of LDG removal on T-SPOT assay ( Zhang et al, 2017 ). In this study, LDGs are removed by PBMCs adherence method and whole blood sedimentation method.…”
Section: Discussionmentioning
confidence: 94%
“…These results confirm that LDGs indeed can inhibit the secretion of IFN-γ in T cells through some mechanism. However, a previous study by Zhang et al had reported an opposite impact of LDG removal on T-SPOT assay ( Zhang et al, 2017 ). In this study, LDGs are removed by PBMCs adherence method and whole blood sedimentation method.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, to normal-density granulocytes (NDG), LDG neutrophils strongly express LDG-specific surface markers (CD10, CD15 and CD16), but, in contrast to NDG, their nucleus is immature [90,91]. LDGs exhibit features of reactive cells.…”
Section: Low-density Granulocytes (Ldg) and Neutrophil Extracellular Traps (Nets) In Aihmentioning
confidence: 99%
“…The number of CD4 + T lymphocytes was assessed using a FACSCalibur type flow cytometer and a tricolor fluorescent antibody labeling kit (BD, USA), as described by Yao et al (2017) and Zhang SG et al (2017). According to the reagent specification, each sample was processed in a TruCONT tube dedicated to flow cytometry.…”
Section: Detection Of Cd4 + T Lymphocytes By Flow Cytometrymentioning
confidence: 99%